An Analysis of Ecolexicon in Petatah Petitih of Minangkabaunese Wedding Ceremony Found in Lintau Buo - Silvi Gusrani; Rusdi Noor Rosa (English Language and Literature, 2020)
This research breaks down about sorts of ecolexicon in pantun of petatah petitih in Minangkabaunese wedding ceremony found in Lintau Buo sub-area. The point of this research is to discover the ecolexicon in the wedding ceremony and its connection to the biological condition of the locale. This research used descriptive qualitative method. The aftereffect of this exploration shows that the most widely recognized sort of ecolexicon discovered is biotic lexicon with flora 10 data, at that point fauna lexicon 7 data and the latter is abiotic lexicon which discovered 10 data. The outcome shows that all ecolexcion utilized in the petatah petitih of the wedding ceremony are additionally found in the ecological environment of the locale.